SGCE missense mutations that cause myoclonus-dystonia syndrome impair ε-sarcoglycan trafficking to the plasma membrane: modulation by ubiquitination and torsinA - Esapa, C; Waite, A; Locke, M; Benson, M; Kraus, M; McIlhinney, R; Sillitoe, R; Beesley, P; Blake, D (Oxford University Press, 2007)
Myoclonus-dystonia syndrome (MDS) is a genetically heterogeneous disorder characterized by myoclonic jerks often seen in combination with dystonia and psychiatric co-morbidities and epilepsy. Mutations in the gene encoding ε-sarcoglycan (SGCE) have been found in some patients with MDS. SGCE is a maternally imprinted gene with the disease being inherited in an autosomal dominant pattern with reduced penetrance upon maternal transmission. In the central nervous system, ε-sarcoglycan is widely expressed in neurons of the cerebral cortex, basal ganglia, hippocampus, cerebellum and the olfactory bulb. ε-Sarcoglycan is located at the plasma membrane in neurons, muscle and transfected cells. To determine the effect of MDS-associated mutations on the function of ε-sarcoglycan we examined the biosynthesis and trafficking of wild-type and mutant proteins in cultured cells. In contrast to the wild-type protein, disease-associated ε-sarcoglycan missense mutations (H36P, H36R and L172R) produce proteins that are undetectable at the cell surface and are retained intracellularly. These mutant proteins become polyubiquitinated and are rapidly degraded by the proteasome. Furthermore, torsinA, that is mutated in DYT1 dystonia, a rare type of primary dystonia, binds to and promotes the degradation of ε-sarcoglycan mutants when both proteins are co-expressed. These data demonstrate that some MDS-associated mutations in SGCE impair trafficking of the mutant protein to the plasma membrane and suggest a role for torsinA and the ubiquitin proteasome system in the recognition and processing of misfolded ε-sarcoglycan.